Bring Your Own Device and Nurse Managers' Decision Making. Issue 2 (February 2017) - Martinez, Karen; Borycki, Elizabeth; Courtney, Karen L.
Abstract : The Bring Your Own Device phenomenon is important in the healthcare environment because this trend is changing the workplace in healthcare organizations, such as British Columbia. At present, there is little research that exists in Canada to provide a distinct understanding of the complexities and difficulties unique to this phenomenon within the nursing practice. This study focused on the experiences and perceptions of nurse managers regarding how they make decisions on the use of personal handheld devices in the workplace. Telephone interviews (N = 10) and qualitative descriptive analysis were used. Four major themes emerged: (1) management perspective, (2) opportunities, (3) disadvantages, and (4) solutions. Nurse managers and other executives in healthcare organizations and health information technology departments need to be aware of the practice and organizational implications of the Bring Your Own Device movement.